The impact of the pandemic on environmental health from the perspective of energy sector - Asri, Novena Damar; Legowo, Evita H; Yusgiantoro, Purnomo (International Journal of Public Health Science (IJPHS), 2024)
This study reviews the impact of the COVID-19 pandemic on environmental health through the energy sector, based on the close relationship between energy, the economy, and the environment. The lockdown policy to contain the spread of the disease has hampered the global economy. Due to the close relationship between energy and the economy, the decline in global economic growth can be easily indicated by the decrease in world energy consumption. However, this study argues that this situation also opens the opportunity of restoring environmental health. Thus, the objective of the study is to find the opportunity and the lesson that can be learned from the COVID-19 pandemic. This study employs a qualitative method that combines descriptive analysis and literature review. It involves a review, processing, and observation of quantitative data (statistics) and qualitative data. This study finds that the pandemic opens opportunities to relieve the environment damaged by fossil-dominated energy consumption to pursue economic growth. However, this study also finds the challenge to overcome and lesson learned. The challenge is the two-way pressure from demand and prices that renewables must face. The lesson to be learned is mainly to reduce the dependency on fossil energy sources, primarily if it is imported. However, on top of that, the government must be able to seize the opportunities to overcome the challenge. Thus, this study is expected to provide an optimistic view of taking advantage of the blessing in disguise of the pandemic to rehabilitate environmental health through the energy sector.